2011
DOI: 10.4049/jimmunol.1003593
|View full text |Cite
|
Sign up to set email alerts
|

Human NK Cells Display Important Antifungal Activity againstAspergillus fumigatus, Which Is Directly Mediated by IFN-γ Release

Abstract: Despite the strong interest in the NK cell-mediated immunity toward malignant cells and viruses, there is a relative lack of data on the interplay between NK cells and filamentous fungi, especially Aspergillus fumigatus, which is the major cause of invasive aspergillosis. By studying the in vitro interaction between human NK cells and A. fumigatus, we found only germinated morphologies to be highly immunogenic, able to induce a Th1-like response, and capable of upregulating cytokines such as IFN-γ and TNF-α. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
108
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 43 publications
10
108
0
3
Order By: Relevance
“…Half of the IFN-g + cells were CD4 + cells, whereas the rest of the IFN-g + cells were negative for this Th cell marker. We were able to demonstrate that a significant number of NK cells express IFN-g, which is in line with a previous report that demonstrated that NK cells play an important role in the antifungal response to A. fumigatus by releasing IFN-g (43). However, in contrast to this, depletion of CD56 + cells did not alter Aspergillus-induced IFN-g responses.…”
Section: Discussionsupporting
confidence: 69%
“…Half of the IFN-g + cells were CD4 + cells, whereas the rest of the IFN-g + cells were negative for this Th cell marker. We were able to demonstrate that a significant number of NK cells express IFN-g, which is in line with a previous report that demonstrated that NK cells play an important role in the antifungal response to A. fumigatus by releasing IFN-g (43). However, in contrast to this, depletion of CD56 + cells did not alter Aspergillus-induced IFN-g responses.…”
Section: Discussionsupporting
confidence: 69%
“…No studies have previously assessed the impact of the inflammasome on the Th1 defense mechanisms during PCM. Because IFN-g is an important cytokine involved in the resistance to P. brasiliensis and other several fungi (11,27,(44)(45)(46)(47)(48)(49)(50), we speculated that IFN-g could play a role in the central mechanism regulated by caspase-1 after P. brasiliensis infection. Confirming this hypothesis, IFN-g production and the Th1 response were lower in infected Asc 2/2 , Casp1 2/2 , and Nlrp3 mice were susceptible to experimental PCM because they exhibited reduced Th1 (and not Th17) immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The exocytosis of cytolytic granules apparently can disrupt fungal germination directly, as evident from the reports that granzyme-deficient mice are susceptible to IFI (41,42). The production of IFN-γ from the D-CAR + T cells may further augment immunity to IFIs, because pharmacological dosing of recombinant IFN-γ (43) or of IFN-γ derived from CD4 + helper T cells or NK cells has been shown to augment anti-Aspergillus activity (44,45). However, it remains to be determined whether the D-CAR-dependent production of IFN-γ can contribute directly to the clearance of fungal infections or indirectly through the activation of granulocytes.…”
Section: Discussionmentioning
confidence: 89%